Willow-Leaf copper MOF networks for efficient oil-water separation and anti-microbial adhesion - Meng Xu; Simin He; Yu Wang; Lang Wei; Jinying Wang; Ruibin Guo; Nijuan Liu; Zunli Mo (Journal of Environmental Chemical Engineering, 2026)

The transcription factor SbWRKY6 confers cadmium tolerance via activating SbPLAC8–17 expression in sorghum - Shan Cao; Jiqing Zhang; Zhengyu Guo; He Wang; Zengting Chen; Simin Li; Na Sui (Journal of Hazardous Materials, 2026)

Corrigendum to “Multimodal luminescence of CaZnGe2O6:Mn2+,Yb3+ phosphors for anti-counterfeiting: dynamic photoluminescence, afterglow, photostimulated luminescence, thermostimulated luminescence and mechanoluminescence” [Chem. Eng. J. 524 (2025) 169152] - Simin Yu; Yujia Gong; Guanlin He; Anfei Chen; Qiaoling Chen; Changkui Duan; Hai Guo (Chemical Engineering Journal, 2026)

Lactobacillus plantarum ameliorates intrahepatic cholestasis by modulating the gut microbiota and tryptophan metabolism - Shijing Dong; Liping Guo; Chenyang Xuan; Chenhui Zhu; Zongze Han; Nian Chen; Xinyu Wang; Meng Shen; Xiaoxuan Wei; Hui Yang; Xue Zhang; Man Liu; et al. (Food Research International, 2026)

Microplastics distribution and impacts on soil microbial communities in alpine area - Taishan Ran; Wei Guo; Yimei Huang; Yixing Guo; Simin Zha; Aowei Wang; Yanxing Dou; Linzhou Dai (Journal of Hazardous Materials, 2026)

Role of heterogeneity of counter-diffusional biofilm on microaeration-assisted for nitrophenol degradation: Metabolic pathways and microbial mechanisms - Zhuowei Zhang; Simin Li; Jing Guo; Yin Yu; Wenhao Hou; Jingye Yang (Journal of Water Process Engineering, 2026)

Provincial policy simulation for steel decarbonization in China: a modular CGE-3E3S coupling framework - Yibo Li; Juan Li; Simin Guo; Mei Sun (Environmental Modelling & Software, 2026)

Melatonin alleviates cholestatic liver injury through modulating gut microbiota and activating the NRF2/HO-1 antioxidant pathway - Shijing Dong; Jiangpeng Liu; Chenyang Xuan; Simin Zhou; Zongze Han; Chenhui Zhu; Nian Chen; Ruiyun Liu; Weirong Wang; Hongyu Chu; Xue Zhang; Hui Yang; et al. (Tissue and Cell, 2026)

Amidoxime-modified PAN@Ce-UiO-66 nanocomposite fiber membrane for efficient removal of Cr(Ⅵ) from water - Yongzhang Qi; Hao Liang; Hebing Pei; Simin He; Hui Zhang; Shijing Li; Shikai Yu; Ruibin Guo; Nijuan Liu; Zunli Mo (Journal of Environmental Chemical Engineering, 2026)

Plant sterol ester-modified naringenin liposomes: A novel strategy for effectively penetrating the mucus barrier - Liuqing Yang; Jingjian Liu; Shuqi Liang; Baihui Guo; Gaodan Liu; Tarun Belwal; Simin Feng (Food Research International, 2025)

Insight into carbon-carbon coupling mechanism for syngas to higher alcohols over agglomeration-induced CuZn catalysts - Simin Du; Penglong Jia; Lei Sun; Chenyang Wang; Haijun Guo; Yongjun Liu; Hui Bai; Danni Xun; Maohong Fan; Wei Huang (Chemical Engineering Journal, 2025)

Analysis of low carbon transformation strategy and CO 2 emission metabolism in the steel industry - Yibo Li; Juan Li; Mei Sun; Simin Guo (Journal of Industrial Ecology, 2025)
As an energy‐intensive sector, the low‐carbon transformation of the steel sector plays a crucial role in achieving China's carbon neutrality goals. Therefore, exploring how learning strategies and incentive mechanisms can synergistically promote the transformation of production and energy structure in the steel sector toward net‐zero emissions is an urgent practical problem that needs to be solved. This study constructed an integrated evaluation framework that combines an improved dynamic computable general equilibrium model with input–output analysis and ecological network analysis, and incorporates learning strategies, carbon taxes, subsidies, carbon trading and other incentive mechanisms into the model to deeply analyze the transformation path of the steel sector in different scenarios. The research not only focuses on the low‐carbon transformation of the steel sector but also comprehensively analyzes the evolution of CO 2 emission metabolism and reveals the complex internal interactions under the background of emission dynamics through a multidimensional network perspective. The results indicate that the steel sector's production and energy structures have significantly changed by implementing incentive mechanisms and introducing learning strategies. In the scenario where carbon taxes, subsidies, and learning strategies work together, it is expected that by 2060, the share of short‐process steelmaking will reach 52.2%, while the proportion of carbon capture and storage equipped in long‐process will exceed 10%. At this time, the short‐process sector's control over other sectors and dependence on the system will increase.

Multimodal luminescence of CaZnGe2O6:Mn2+,Yb3+ phosphors for anti-counterfeiting: dynamic photoluminescence, afterglow, photostimulated luminescence, thermostimulated luminescence and mechanoluminescence - Simin Yu; Yujia Gong; Guanlin He; Anfei Chen; Qiaoling Chen; Changkui Duan; Hai Guo (Chemical Engineering Journal, 2025)

Development of fluorine-free superhydrophobic antibacterial and antifouling coatings: A multifunctional composite system for biomedical materials and metal protection - Meng Xu; Simin He; Yu Wang; Rongkai Li; Lang Wei; Ruibin Guo; Nijuan Liu; Zunli Mo (Chemical Engineering Journal, 2025)

Human gut Bifidobacterium longum subsp. suillum is enriched in vitro by a pectic polysaccharide isolated from the flowers of Lilium lancifolium - Meixia Li; Renjie Liu; Tao Wang; Lana Duo; Guo Chen; Mengfei Mao; Yue Sun; Yun Li; Simin Cai; Wanqi Zhou; Haibiao Lai; Kan Ding (Carbohydrate Polymers, 2025)

Multi-asymmetry on residual sediment transport in the branching channels of the Yangtze Estuary - Simin Zhou; Chunyan Zhu; Jianliang Lin; Weiming Xie; Naiyu Zhang; Leicheng Guo; Qing He (Journal of Hydrology, 2025)

Numerical study on the stability of offshore pile-soil systems considering pore pressure response induced by extreme storms - Simin Xu; Xiaolei Liu; Cheng Zhang; Hong Zhang; Botao Xie; Xingsen Guo (Ocean Engineering, 2025)

Simple synthesis and excellent performance of the cow dung–based biodegradable liquid mulch for sustainable agriculture - Xiaohao Guo; Yuankai Zhou; Simin Li; Zhiwen Li; Wei Liu; Yalan Zhang; Hu Du; Wenrong Xiong; Qi Li; Yanyan Zhong; Tian Qin; Mengting Wu; et al. (Environmental Research, 2025)

Water-stabilized perovskite CsPbBr3/CsPb2Br5 for high-sensitivity fluorescence “on-off-on” recognition and cell imaging - Simin He; Rongkai Li; Meng Xu; Yu Wang; Ruibin Guo; Nijuan Liu; Zunli Mo (Chemical Engineering Journal, 2025)

Melatonin protects bovine oocyte from βHB-induced oxidative stress through the Nrf2 pathway - Kaiyan Zhang; Jing Guo; Simin Wang; Changguo Min; Jun Wang; Hongyu Liu; Yi Fang; He Ding; Jing Zhao; Xin Ma; Wenfa Lu (Theriogenology, 2025)

Versatile benzthienocarbazole isomer derivatives as efficient TADF emitters and hosts for blue multi-resonance TADF emitters - Deli Li; Jiaji Yang; Simin Jiang; Haoxiang Yuan; Denghui Liu; Zhihai Yang; Guo-Xi Yang; Mengke Li; Xuchuan Jiang; Wei Li; Shi-Jian Su (Chemical Engineering Journal, 2025)

Ambient ultrafine particles exacerbate oxygen desaturation during sleep in patients with chronic obstructive pulmonary disease: New insights into the effect spectrum of ultrafine particles on susceptible populations - Wenlou Zhang; Baiqi Chen; Yoshiko Yoda; Masayuki Shima; Chen Zhao; Xuezhao Ji; Junyi Wang; Sha Liao; Simin Jiang; Luyi Li; Yahong Chen; Xinbiao Guo; et al. (Science of The Total Environment, 2024)

Inorganic salts released from polypyrrole nanocapsules on compact TiO2 layer for highly efficient inorganic CsPbI3-type perovskite solar cells - Dan Li; Xin Li; Kang Wang; Simin Ma; Xin Shao; Tingting Yang; Yunhui Han; Zhengguo Zhang; Shengzhong Liu; Shengwei Guo (Chemical Engineering Journal, 2024)

Numerical Investigation into the Stability of Offshore Wind Power Piles Subjected to Lateral Loads in Extreme Environments - Miaojun Sun; Zhigang Shan; Wei Wang; Simin Xu; Xiaolei Liu; Hong Zhang; Xingsen Guo (Journal of Marine Science and Engineering, 2024)
Monopile foundations are extensively utilized in the rapidly expanding offshore wind power industry, and the stability of these foundations has become a crucial factor for ensuring the safety of offshore wind power projects. Such foundations are subjected to a myriad of complex environmental loads during their operational lifespan. Whilst current research predominantly concentrates on the effects of wind, wave, and current loads on monopile stability in extreme environments, it is imperative to consider the potential influence of unexpected submarine landslide loads. In this study, we provide a comprehensive overview of wind, wave, current, and submarine landslide loads on monopile foundations in extreme environments. Subsequently, we establish a finite element model for analyzing the stability of monopiles under complex lateral loads, and validate the accuracy of the model by comparing it with the previous numerical findings. A case study is performed with reference to the Xiangshui Wind Farm project to analyze the effects of varying submarine landslide densities, velocities, impact heights, and seabed sediment strengths on pile head horizontal displacement, pile rotation at the mudline, and maximum bending moment. The findings indicate that the increase in submarine landslide density, velocity, and impact height leads to an increase in horizontal displacement at the pile head, pile rotation at the mudline, and maximum bending moments, and a horizontal failure mode is observed in seabed sediments. Furthermore, under the same load conditions, a decrease in seabed sediment strength and internal friction angle triggers instability in monopiles, with a noteworthy transition from horizontal failure to deep-seated seabed sediment failure. Finally, we propose a criterion for monopile instability under diverse loading conditions.

Influence of the Species Number of Hydrometeors on Numerical Simulation of the Super Typhoon Mujigae in 2015 - Simin Pang; Jiangnan Li; Tianyun Guo; Xiaoling Ma (Asia-Pacific Journal of Atmospheric Sciences, 2024)

Altered functional brain networks in coronary heart disease: independent component analysis and graph theoretical analysis - Simin Lin; Puyeh Wu; Shaoyin Duan; Qianni Du; Shujia Guo; Zhishang Chen; Naiming Wu; Xiaoyan Chen; Ting Xie; Yi Han; Hengyu Zhao (Brain Structure and Function, 2023)

Influence of surface layer schemes on tropical cyclone Hato (2017) intensity - Xiaoling Ma; Jiangnan Li; Simin Pang; Tianyun Guo; Chenghui Ding (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Enantioselective effects of paclobutrazol and its enantiomers on glycolipid metabolism in zebrafish (Danio rerio) - Dong Guo; Simin Chen; Weiguang Zhang; Jun Fan (Pesticide Biochemistry and Physiology, 2023)

Association of multiple air pollutants with oxygen saturation during sleep in COPD patients: Effect modification by smoking status and airway inflammatory phenotypes - Wenlou Zhang; Junyi Wang; Baiqi Chen; Xuezhao Ji; Chen Zhao; Maike Chen; Sha Liao; Simin Jiang; Zihan Pan; Wanzhou Wang; Luyi Li; Yahong Chen; et al. (Journal of Hazardous Materials, 2023)

Prediction and sensitivity analysis of chlorophyll a based on a support vector machine regression algorithm - Li Xu; Guizhen Hao; Simin Li; Fengzhi Song; Yong Zhao; Peiran Guo (Environmental Monitoring and Assessment, 2023)

Spiral donor-based host materials for highly efficient blue thermally activated delayed fluorescence OLEDs - Deli Li; Mengke Li; Wei Li; Wenqi Li; Zijian Chen; Xiaomei Peng; Denghui Liu; Guo-Xi Yang; Simin Jiang; Yiyang Gan; Zhihai Yang; Kunkun Liu; et al. (Chemical Engineering Journal, 2023)

Planar D-σ-A type thermally activated delayed fluorescence material with Intra- and intermolecular charge transfer characteristics - Simin Jiang; Jianyin Lin; Deli Li; Mengke Li; Yanmei He; Wentao Xie; Jiting Chen; Yiyang Gan; Guo-Xi Yang; Zhihai Yang; Wei Li; Shi-Jian Su (Chemical Engineering Journal, 2023)

Small Jellyfish as a Supplementary Autumnal Food Source for Juvenile Chaetognaths in Sanya Bay, China - Lingli Wang; Minglan Guo; Tao Li; Hui Huang; Sheng Liu; Simin Hu (Journal of Marine Science and Engineering, 2020)
Information on the in situ diet of juvenile chaetognaths is critical for understanding the population recruitment of chaetognaths and their functional roles in marine food web. In this study, a molecular method based on PCR amplification targeted on 18S rDNA was applied to investigate the diet composition of juvenile Flaccisagitta enflata collected in summer and autumn in Sanya Bay, China. Diverse diet species were detected in the gut contents of juvenile F. enflata, including copepods, small jellyfish, anthozoa, polychaetes, echinoderms, diatoms and dinoflagellates. The diet composition showed obvious differences between summer and autumn. Copepod, such as Temora turbinata, Canthocalanus pauper and Subeucalanus crassus, dominated the diet in summer, representing up to 61% of the total prey items. However, small jellyfish, mainly consisting of Bougainvillia fulva, Solmissus marshalli and Pleurobrachia globosa, was the main food group (72.9%) in autumn. Environmental parameters showed no significant difference between summer and autumn. The mean abundance of juvenile chaetognaths in autumn was about eight times higher than that in summer, while the abundance of potential food prey was similar in both seasons. Our results suggested that juveniles chaetognaths might consume small jellyfish as a supplementary food source under enhanced feeding competition in autumn.

Flexible feeding patterns of copepod Centropages tenuiremis in fluctuating conditions: a possible survival strategy to cope with disturbance - Cuilian Xu; Simin Hu; Zhiling Guo; Tao Li; Hui Huang; Leo Lai Chan; Sheng Liu (Acta Oceanologica Sinica, 2020)

Dibenzoylmethane Protects Against CCl4-Induced Acute Liver Injury by Activating Nrf2 via JNK, AMPK, and Calcium Signaling - Mingnan Cao; Huixia Wang; Limei Guo; Simin Yang; Chun Liu; Tin Oo Khor; Siwang Yu; Ah-Ng Kong (The AAPS Journal, 2017)